Ruiny architektury sakralnej. Śmierć miejsca - śmierć sacrum? - Nieszczerzewska, Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
The main topic of the article is sacred, but abandoned, derelict and forgotten places. The author pays particular attention to the issue of an ontological status of a sacred ruin as a non-place and the issue of the disappearing sacredness which once defi ned abandoned architecture. A ruin is designated a non-place as a result of a phenomenological definition of a place as a point in space with a particular identity. The author tries to answer the question of whether sacral architecture can still function as a place after it has been abandoned and is no longer present in the experience of ordinary people.